2010
DOI: 10.1161/hypertensionaha.109.148999
|View full text |Cite
|
Sign up to set email alerts
|

Amlodipine-Valsartan Combination Decreases Central Systolic Blood Pressure More Effectively Than the Amlodipine-Atenolol Combination

Abstract: Abstract-The ␤-blocker atenolol is less effective than angiotensin-receptor blockers and calcium-channel blockers for reducing central blood pressure (BP). The trial was designed to determine whether the advantages of angiotensinreceptor blockers over atenolol remained significant when both were combined with the calcium-channel blocker amlodipine. A prospective, randomized, blinded endpoint (PROBE design) parallel group, multicenter trial including 393 patients with essential hypertension resistant to 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
106
0
31

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(153 citation statements)
references
References 41 publications
12
106
0
31
Order By: Relevance
“…Recent studies have shown a BP-independent association between muscular nerve sympathetic activity and aortic PWV (19,20), suggesting that suppression of sympathetic nervous system under b-blockade could be a functional regulator of regression in arterial stiffness. In addition to the above, the results of this study are supported by several randomized studies conducted in the general hypertensive population, in which nonvasodilating b-blockers reduced PWV to a similar (21)(22)(23) or even higher (24,25) (21). Similarly, in a subgroup of 114 patients with hypertension participating in the Conduit Artery Function Evaluation Study, treatment for almost 5 years with the perindopril/amlodipine combination lowered aortic PWV to a similar extent as the atenolol/thiazide regimen (23).…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have shown a BP-independent association between muscular nerve sympathetic activity and aortic PWV (19,20), suggesting that suppression of sympathetic nervous system under b-blockade could be a functional regulator of regression in arterial stiffness. In addition to the above, the results of this study are supported by several randomized studies conducted in the general hypertensive population, in which nonvasodilating b-blockers reduced PWV to a similar (21)(22)(23) or even higher (24,25) (21). Similarly, in a subgroup of 114 patients with hypertension participating in the Conduit Artery Function Evaluation Study, treatment for almost 5 years with the perindopril/amlodipine combination lowered aortic PWV to a similar extent as the atenolol/thiazide regimen (23).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, several studies have demonstrated that brachial BP is not a good surrogate for the hemodynamic effects of drug therapies on central circulation. The recently published EX-PLOR Study 5 and the Conduit Artery Function Evaluation Study 6 clearly demonstrated that angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and calcium channel blockers have a more pronounced effect on reducing central BP compared with the cardioselective ␤-blocker (BB) atenolol. Different effects of BB on central BP can explain the findings of a recent meta-analysis published by Law et al, 7 which demonstrates a slight inferiority of BB in preventing stroke.…”
mentioning
confidence: 99%
“…During this study we administered FSCs only, which cannot exert oncogenic properties and within the whole period of our practice we did not experience likely processes among the patients. One more possible effect in human after FSCs transplantation is a potential to reject stem cells; however, since HLA receptors are immature in embryonic fetuses of 7-12 weeks of gestation [28,29]; such a graft-versus-host reaction is not the case. No similar cases were recorded based on general clinical criteria during our study either.…”
Section: Discussionmentioning
confidence: 99%